Diwan of Ibn al-Tathariyya, a stylistic study The twenty-sixth poem is an example - نجّاري, هويدا (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
Ibn al-Tathriyya was one of the poets of the Umayyad era, and a model of a sober poetic voice that preserved the Khalili poetic template. His poetic experience expanded and extended over many years of his life, During which he produced a collection of poetry filled with sentiments, especially since he was one of those who were known for love and famous for it, and he was one of the pioneers in that era, His poem (Evening of Youth) tells a story of regret for his departed youth, the loss of contact with goodness, and a prayer to God to overcome the many incidents that made him wise and reject hatred and harm. This poem has seventeen lines, full of the beauties of grammar and rhetoric, which makes it rich material for stylistic reading, which is what we studied in this research, Through studying the phonetic level, which studies the internal rhythm with its elements repetition, the use of loudness and whispering, alliteration, and slurring, and the external rhythm with its elements meter, rhyme, and narration, The morphological level studies the derivational forms such as the active participle, the passive participle, the modal adjective, the exaggeration of the participle and the noun of place. It also studies the inanimate noun with its two types: the inanimate meaning and the inanimate object, The synthetic level, which studies the declarative style in its primary, requesting, and denial types, and the constructional style, with its various types of call, command, exclamation, and oath, and also studies nominal sentences, semi-sentences, verbal sentences, and rhetorical structures, The semantic level is through the study of semantic fields and suggestive words.